Clinical Trials of Novel Targeted Therapies in Ovarian Cancer: Moving Beyond Poly ADP Ribose Polymerase (PARP) Inhibitors - Guo, Quan; Yang, Qing; Li, Jun; Liu, Guipeng; Nikoulin, Igor; Jia, Steve (Current Pharmaceutical Biotechnology, 2018)
Background: Epithelial ovarian cancer (EOC) is one of the most common cancers in the female reproductive system and deadliest gynecological cancer in the United States. Standard treatments by surgery and platinum-based chemotherapy are not satisfied for the patients with high risk of relapse. Advances in molecular biology for EOC development have brought several targeted therapies to benefit recurrent patients. Poly-ADP-ribose polymerase inhibitors (PARPi) may be one of the most successful classes of targeted therapies with three approved medicines. For better clinical outcomes and more comprehensive disease management of EOC, more novel classes of targeted therapies are needed. Method: We focus on non-PARPi novel targeted therapies that are completed or on-going in phase III clinical trials by searching databases of Pubmed and Clinicaltrials.gov. Keywords of “ovarian cancer, targeted therapy and phase III trial” were used for publications and information from May 2012 to May 2018. Results: There are total 150 viable EOC phase III studies listed in Clinicaltrials.gov., including 20 completed studies with results and 73 on-going studies. Bevacizumab plus chemotherapy is the only medication with government approval for recurrent EOC. Targeted therapies against other growthrelated factors, cytokines and folate receptor are failed in phase III trials or still on-going. Conclusion: Implications of on-going phase III trials are: 1) combination therapy of bevacizumab with atezolizumab may be the most anticipated studies for approvals; 2) mirvetuximab soravtansine plus chemotherapy may generate positive results to justify an approval; and 3) Immune therapy for EOC may bring new treatments for the patients.
Keywords: Clinical trial